The Roles of Peyer's Patches and Microfold Cells in the Gut Immune System: Relevance to Autoimmune Diseases - Kobayashi, Nobuhide; Takahashi, Daisuke; Takano, Shunsuke; Kimura, Shunsuke; Hase, Koji (Frontiers in Immunology, 2019)
Microfold (M) cells are located in the epithelium covering mucosa-associated lymphoid tissues, such as the Peyer’s patches (PPs) of the small intestine. M cells actively transport luminal antigens to the underlying lymphoid follicles to initiate an immune response. The molecular machinery of M-cell differentiation and function has been vigorously investigated over the last decade. Studies have shed light on the role of M cells in the mucosal immune system and have revealed that antigen uptake by M cells contributes to not only mucosal but also systemic immune responses. However, M-cell studies usually focus on infectious diseases; the contribution of M cells to autoimmune diseases has remained largely unexplored. Accumulating evidence suggests that dysbiosis of the intestinal microbiota is implicated in multiple systemic diseases, including autoimmune diseases. This implies that the uptake of microorganisms by M cells in PPs may play a role in the pathogenesis of autoimmune diseases. In this review, we focus on the relationship between M cells and commensal bacteria in autoimmune diseases. We provide an outline of the current understanding of M-cell biology and subsequently discuss the potential contribution of M cells and PPs to the induction of systemic autoimmunity, beyond the mucosal immune response.